Riot grrrl gaming: gender, sexuality, race, and the politics of choice in Gone Home. Issue 3 (4th May 2019) - Tulloch, Rowan; Hoad, Catherine; Young, Helen
ABSTRACT: In this article, we provide a critical analysis of the mystery/adventure video game Gone Home to demonstrate how the game resists norms of contemporary gaming by drawing on a tradition of feminist action in cultural spaces. In interrogating the ways in which Gone Home invokes the aesthetics, identities, and political strategies of the 1990s riot grrrl scene, we argue that Gone Home, in its centring of women's narratives, collective feminist agency, and deliberate disavowal of unrestricted choice, can be read as a piece of riot grrrl art. Such 'riot grrrl gaming', wherein the narrative gameplay of Gone Home mobilizes riot grrrl feminist action, is a pertinent rejoinder to exclusory, and often violently misogynistic, contemporary gaming culture. However, in critically engaging with how Gone Home interpellates riot grrrl, both through its aesthetics and its game play, we argue that the game nonetheless retains white hegemony as a problematic central tenet of both the riot grrrl movement and gaming. This article thus argues that Gone Home disrupts the dominant gender and sexual politics of gaming, yet simultaneously reinstates deeply problematic racial politics, and in doing so calls attention to the need for intersectionality in the cultural spaces of gaming.